Continuous wall conditioning VHF discharge without magnetic field in a toroidal device - Lozin, A.V.; Moiseenko, M.M.; Kozulya, M.M.; Kramskoj, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Grigor’eva, L.I.; Beletskii, A.A.; Shapoval, A.N.; Makhov, M.M.; Krasyuk, A.Yu.; Baron, D.I. (Вопросы атомной науки и техники, 2016)
Experiments were carried out at Uragan-2M torsaron for wall conditioning without magnetic field. Plasma
discharge was created with the same antenna and VHF generator used for weak magnetic field (B0=100 G) wall
conditioning. Experiment was carried out during whole wall conditioning period of Uragan-2M experimental
campaign. The dynamics of wall conditioning was obtained alongside with standard plasma parameters
measurements. На торсатроне Ураган-2М был выполнен модельный эксперимент по чистке стенок вакуумной камеры
без магнитного поля. Плазменный разряд создавался той же антенной и СВЧ-генератором, которые
использовались для чистки в слабом магнитном поле (B0=100 Гс). Эксперимент проводился на протяжении
всего периода чистки во время экспериментальной кампании Урагана-2М. Динамика чистки стенок была
получена вместе со стандартными измеряемыми параметрами плазмы. На торсатроні Ураган-2М було проведено модельний експеримент із чистки стінок вакуумної камери без
магнітного поля. Плазмовий розряд створювався тією самою антеною та НВЧ-генератором, що
використовуються для чистки в слабкому магнітному полі (B0=100 Гс). Експеримент проводився впродовж
всього періоду чистки пiд час експериментальної кампанії Урагана-2М. Динаміка чистки стінок була
отримана разом із стандартними вимірюваними параметрами плазми.